Effects of Filipino Consumers’ Financial Attitudes, Subjective Norms, and Perceived Behavioral Control on Intentions to Formal Banking: Towards Financial Inclusion - Co, Manuelito; Centeno, Dave DG. (Philippine Management Review; Vol 30 (2023), 2023)
This study analyzes the role of attitudes, subjective norms, and perceived behavioral control on the behavioral intentions of Filipinos in saving surplus money in the bank. Anchoring on the theory of planned behavior, a logistic model involving this financial behavioral intention and psychological variables extracted from the Philippine Central Bank’s Consumer Finance Survey was developed. The survey generated data through a stratified random sampling of households asking their financial conditions including income, spending and insurance coverage. Findings illustrate that subjective norms and perceived behavioral control significantly predict behavioral intention towards banking. Moreover, demographic differences are also described to influence behavioral intentions. Implications and contributions are positioned in the contextualization of psychological factors in consumer finance domain and consequently towards financial inclusion marketing strategies.